Semiconductors from book to breadboard : complete textbook/lab manual - McGowan, Kevin A. (Australia : Cengage Learning Asia Pte Ltd, 2012)
Offers a user-friendly approach to understanding solid-state devices. This title focuses on the concepts and skills entry-level electronics technicians need to be successful. It identifies, tests, and troubleshoots discrete and integrated semiconductor devices, such as diodes, transistors, and op amps.
Section I: DIODES. 1. Semiconductor Principles and the PN Junction Diode. 2. Special Purpose Diodes and Their Applications. 3. Rectifiers and Power Supplies. Section II: TRANSISTORS. 4. Bipolar Junction Transistors (BJTs). 5. Amplifier Configurations. 6. Amplifier Classes. 7. Field-Effect Transistors. Section III: ADVANCED SEMICONDUCTOR DEVICES AND APPLICATIONS. 8. Operational Amplifiers. 9. Oscillators. 10. Semiconductor Control Devices. Section IV: RESOURCES.
Includes index.